Usulan Perbaikan Sistem Untuk Meningkatkan Kualitas Layanan Sistem Administrasi Gudang Online (AGO) Menggunakan Standar ISO/IEC 9126 di PT. PLN (Persero) Rayon Duri - Muhammad Ihsan Hamdy; Rika Rahmat Putri (Universitas Putra Indonesia YPTK Padang, 2019)
In building a system, it was needed a quality guarantee. A system could be stated well qualified, if it met the user needs. The quality could be measured from various points of views. One point of views to measure the software quality was focusing on user satisfaction (user based). To know the quality of a system, it was needed a quality analysis of its system. There was a lack of service when online warehouse administration system used to manage the warehouse material inventory in PT. PLN (Persero) Duri Rayon was used. This research aimed at finding proposed improvements for increasing the service quality percentage of online warehouse administration system based on ISO/IEC 9126 standard. The methods of collecting the data were using interview and questionnaire to know user complaints to the user. Maturity Model and Delay approaches were used to process the data. In testing the reliability level, online warehouse administration system was on the first level (the system was computerized, but it was not standardized yet). In testing the delay, all the delays in input were on good category and it could beunderstandable. Based on the levels of maturity and delay, the test showed that there was a need to improve and maintenance the online warehouse administration system to increase the performance of system service quality for users. so that the existence of repairs and maintenance systems can increase 26% to 41% the percentage of the quality of an information technology system.